T Cell Subpopulations in Healthy Elderly and Lung Cancer Patients: Insights from Cuban Studies - Saavedra, Danay; Garcia, Beatriz; Lage, Agustin (Frontiers in Immunology, 2017)
The senescence of the immune system and the risk of cancer both increase with aging. Age itself entails changes in the immune system, which are related with a decrease in thymic output of naïve lymphocytes, the accumulation of chronic antigenic load, notably chronic viral infections such as cytomegalovirus, and replicative senescence of lymphocytes. These changes could eventually contribute to cancer risk and to response to cancer treatment but several confounding factors make it difficult to draw a picture of causal relationships. Studies in diverse human populations could contribute to clarify these complex relationships. Here we summarize the current knowledge about the senescence of the T cells, the relationship with CMV infection, cancer and cancer treatment and the results of a series of studies performed in Cuba, a population characterized by the unusual combination of long life expectancy together with the high antigenic load, including cytomegalovirus infection, typical of a tropical country. Although immunosenescence affects almost all components and function of the immune response its most salient feature is a decrease in numbers and proportions of naïve CD8 T lymphocytes together with an accumulation of highly differentiated effector-memory CD8 T lymphocytes. These features were confirmed in the Cuban studies but a clear gender effect also appeared. As the global population ages, a rapid increase in elderly people with malignant tumors can be expected; therefore, a comprehensive evaluation of patient’s immune status would provide an appropriate support for determining whether patients are going to be benefitted with immunotherapy.